Optimizing Water Quality in Carp Farming through an IoT-based Dissolved Oxygen Monitoring System - Khusnul Hayati; Faishal Arham Pratikno; Putri Gesan Prabawa Anwar; Healty Susantiningdyah (Universitas Islam Raden Rahmat, Malang, 2025)
Dissolved oxygen (DO) is a critical parameter in common carp (Cyprinus carpio) aquaculture, as low DO levels can cause stress, inhibit growth, and lead to fish mortality. Conventional measurement methods, such as manual titration or DO meters, are limited because they cannot provide continuous or real-time monitoring. Therefore, this study aims to develop an Internet of Things (IoT)-based dissolved oxygen monitoring system using the Waterfall development method to maintain optimal water quality in carp ponds. The system utilizes an ESP32 microcontroller, a DO sensor, and the Blynk platform as a real-time remote monitoring interface. It continuously measures DO levels, displays data locally on an LCD, and sends automatic notifications when the DO value falls below 5 mg/L. Field testing was conducted for one week at the Rama Graha carp pond, showing that the system achieved an accuracy of 92.7%, an error rate of 7.3%, and a precision of 98%. The developed system effectively supports farmers in maintaining stable water quality and reducing fish mortality. This study contributes to the development of practical, low-cost IoT technology for sustainable freshwater aquaculture management.